Identification of Multimodal Dynamic Characteristics of a Decurrent Tree with Application to a Model-Scale Wind Tunnel Study - Zhengnong Li; Yanfeng Hao; Gregory A. Kopp; Chieh-Hsun Wu (Applied Sciences, 2022)
Wind tunnel tests of scaled model trees provide an effective approach for understanding fluctuating wind loading and wind-induced response of trees. For decurrent trees, vague multimodal dynamic characteristics and ineffective estimation of leaf mass are two of the main obstacles to developing aeroelastic models. In this study, multimodal dynamic characteristics of the decurrent tree are identified by field measurements and finite element models (FEM). It was found that the number of branches swaying in phase determines the magnitude of effective mass fraction of branch modes. The frequencies of branch modes with larger effective mass fraction were considered as a reference for an aeroelastic model. In addition, an approach to estimate leaf mass without destruction was developed by comparing trunk frequency between field measurements and FEM. Based on these characteristics of the prototype, the scaled, aeroelastic model was constructed and assessed. It was found that the mismatch of leaf stiffness between the model and the prototype leads to mismatch of leaf streamlining and damping between them. The Vogel exponent associated with leaf streamlining provides a possible way to ensure consistency of leaf stiffness between the model and prototype.